Social norms and naïve beliefs - Amrish Patel; Edward Cartwright (University of Kent, Department of Economics, 2009)
In this paper we analyse the effect that naïve agents (those who take behavior at 'face value') have on the nature of social norms. After reviewing the use of signalling models to model conformity, we argue in favour of modelling naïve inferences in tandem with standard Bayes rational inferences. Naïve agents weaken the existence of social norms and reduce the range of actions that can become social norms.
Keywords: D82; D83; Z13; 330; signalling; conformity; social norms; naïve beliefs; Soziale Werte; Altruismus; Öffentliches Gut; Signalling